The Association between Vitamin D3 Deficiency and Cataract Formation in Baghdad Al-Karkh - Raad Saeed , Hiba; Ghazi Dadoosh, Ahmed; Mohamad Ali, Besmah; Awad Mohamed Elbassiouny, Khaled (Diyala Journal of Medicine, 2024)
Background: Visual impairment is a global issue that is particularly problematic for poor nations. It is linked to diminished physical activity, social isolation, reliance on everyday tasks, and even death. The clouding of the lens inside the eye is called a cataract. It is one of the main causes of blindness and visual impairment in the world. Because of its anti-inflammatory and antioxidant properties, vitamin D, a prohormone in the blood, is crucial to the pathophysiology of many ocular illnesses. Given that oxidative stress and inflammation are significant contributors to the development of cataracts, a number of research have evaluated the relationship between vitamin D3 deficiency and cataract formation. Objective: Determine whether a vitamin D3 deficiency and cataracts are related. Patients and Methods: A cross-sectional study that was carried out included a total of 100 cataract patients who are 60 years of age or younger from September 2023 to March 2024 in the Ophthalmology Department of Imamein Kadhimein Medical City, Baghdad, Iraq. Questionnaire form was used which consist of sociodemographic information, socioeconomic status, dietary sources of vitamin D3, sun exposure, anthropometric measures and ophthalmic examination. Vitamin D3 level had been investigated in laboratory of the hospital. Results: Thirty percent of patients had cortical cataracts, 57% had nuclear cataracts, and 13% had posterior subcapsular cataracts. Sixty-nine percent of patients had a vitamin D3 level that is less than 20 ng/ml. Of the patients, 13% had a vitamin D3 level between 20 and 30 ng/ml, while 18% had a level greater than 30 ng/ml. There is a significant association between the level of vitamin D3 and the type of cataract (p-value = 0.013). Sixty-nine percent of patients with deficient vitamin D3 levels had 9% posterior subcapsular cataracts, 36% cortical cataracts, and 55% nuclear cataracts. Patients with insufficient vitamin D3 levels had 8% posterior subcapsular cataracts, 8% cortical cataracts, and 84% nuclear cataracts. While patients with sufficient vitamin D3 levels had 33% posterior subcapsular cataracts, 22% cortical cataracts, and 45% nuclear cataracts. The body mass index and vitamin D3 level were significantly associated (p-value = 0.003). Patients with a vitamin D3 level less than 20 ng/ml comprised 31% overweight patients, 26% class I obese patients, 26% class II obese patients, and 4% class III obese patients. Thirteen percent of these patients had normal weights. Patients with a vitamin D3 level 20-30 ng/ml comprised 46% overweight patients, 23% class II obese patients, and 31% with normal weight. While patients with a vitamin D3 level more than 30 ng/ml comprised 33% normal weight patients and 67% overweight. Conclusion: Vitamin D3 deficiency has a significant association with cataract formation, especially nuclear and cortical types, sun exposure, educational level, socioeconomic status, and obesity.